2014
DOI: 10.1039/c4dt01750a
|View full text |Cite
|
Sign up to set email alerts
|

Coordination chemistry of Co complexes containing tridentate SNS ligands and their application as catalysts for the oxidation of n-octane

Abstract: The selective oxidation of saturated hydrocarbons to terminal oxygenates under mild catalytic conditions has remained a centuries long challenge in chemical catalysis. In an attempt to address this challenge, two series of tridentate donor ligands {2,6-bis(RSCH2)pyridine and bis(RSCH2CH2)amine [R = alkyl, aryl]} and their respective cobalt complexes {Co[2,6-bis(RSCH2)pyridine]Cl2 and Co[bis(RSCH2CH2)amine]Cl2} were synthesized and characterized. Crystal structures of Co[2,6-bis(RSCH2)pyridine]Cl2 [R = -CH3 (),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 51 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…The central Co II atom, located on a crystallographic center of inversion, is coordinated by two N and two S atoms from two symmetry-equivalent ligands 1 situated in the equatorial plane and two Cl atoms in the axial positions. The Co-N [2.1543 (17) A ˚] and Co-S [2.4856 (5) A ˚] bond lengths are within the range of those found in dichloridocobalt(II) complexes with a nitrogen-and sulfur-containing multidentate ligand (Soobramoney et al, 2014;Lei et al, 2018). In addition, weak intermolecular C-HÁ Á Á interactions between the 8-(benzylsulfanyl)quinoline ligands are data reports observed in the crystal packing of 2 (Karle et al, 2007), forming a chain along the a-axis direction (Fig.…”
Section: Structure Descriptionmentioning
confidence: 62%
See 1 more Smart Citation
“…The central Co II atom, located on a crystallographic center of inversion, is coordinated by two N and two S atoms from two symmetry-equivalent ligands 1 situated in the equatorial plane and two Cl atoms in the axial positions. The Co-N [2.1543 (17) A ˚] and Co-S [2.4856 (5) A ˚] bond lengths are within the range of those found in dichloridocobalt(II) complexes with a nitrogen-and sulfur-containing multidentate ligand (Soobramoney et al, 2014;Lei et al, 2018). In addition, weak intermolecular C-HÁ Á Á interactions between the 8-(benzylsulfanyl)quinoline ligands are data reports observed in the crystal packing of 2 (Karle et al, 2007), forming a chain along the a-axis direction (Fig.…”
Section: Structure Descriptionmentioning
confidence: 62%
“…Dichloridocobalt(II) complexes with hetero donor ligands (e.g., nitrogen-and sulfur-containing multidentate ligands) also exhibit interesting catalytic activities, e.g. in the oxidation reaction of n-octane (Soobramoney et al, 2014) and in the photochemical-driven hydrogen evolution from water (Lei et al, 2018); however, they are still limited in number. Herein, we report the structure determination of a new dichloridocobalt(II) complex 2 with 8-(benzylsulfanyl)quinoline (1) as an N,S-ligand (Kita et al, 2002) by single-crystal X-ray analysis.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…Our study commenced with the preparation of the SNS pincer ligand 19a using literature reported protocols [ 36 ] as shown in Scheme 1 . Treatment of in situ-generated thiophenolate with 2,6-bis(chloromethyl)pyridine ( 18 ) afforded pincer ligand 19a in 73% yield.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 In this work, a new approach has been undertaken in using cobalt aminodiphosphine complexes in the C-H activation of n-octane. 40,45 Phosphine based ligands have not been widely explored due to ligand degradation or loss of ligand from the metal complex. [31][32][33][34] The development of synthetic models has been biologically inspired by a number of enzymes such as methane monooxygenase and cytochrome P450, which make use of a reactive iron-oxo species in the oxidation of a number of alkanes.…”
Section: Introductionmentioning
confidence: 99%
“…3,17,[42][43][44] More recently Tordin and coworkers have used cobalt complexes with tripodal 4N ligands in the oxidation of alkanes, while SNS cobalt complexes have also been studied in the oxidation of noctane. 40,45 Phosphine based ligands have not been widely explored due to ligand degradation or loss of ligand from the metal complex. 46 However, Wong and co-workers have used ruthenium based phosphine complexes in the oxidation of noctane and reported low conversions.…”
Section: Introductionmentioning
confidence: 99%